2022
DOI: 10.14245/ns.2143210.605
|View full text |Cite
|
Sign up to set email alerts
|

Glioma Immunotherapy: Advances and Challenges for Spinal Cord Gliomas

Abstract: Objective: Spinal cord gliomas are rare entities that often have limited surgical options. Immunotherapy has shown promise in intracranial gliomas with some research suggesting benefit for spinal cord gliomas.Methods: A focused review of immunotherapies that have been investigated in spinal cord gliomas was performed. Results:The primary methods of immunotherapy investigated in spinal cord gliomas include immune checkpoint inhibitors, adoptive T cell therapies, and vaccine strategies. There are innumerable cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 106 publications
(356 reference statements)
0
20
0
Order By: Relevance
“…However, the previous study reported that gross-total resection followed by radiotherapy had beneficial effects on the overall outcome of PSC GB in the pediatric age group[ 23 , 24 ]. More effective and targeted therapies need specific investigation in the future for helping patients with unique gene mutations achieve better prognosis[ 25 , 26 ]. Further, broadening treatment avenues would help improve the efficacy of therapies and help in recovery for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the previous study reported that gross-total resection followed by radiotherapy had beneficial effects on the overall outcome of PSC GB in the pediatric age group[ 23 , 24 ]. More effective and targeted therapies need specific investigation in the future for helping patients with unique gene mutations achieve better prognosis[ 25 , 26 ]. Further, broadening treatment avenues would help improve the efficacy of therapies and help in recovery for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The BBB and relative immunologic privilege of the brain are doubtless factors in GBM ranking among the immunologically cold cancer types [15]. Clinical trials of various immunotherapeutic strategies in patients with GBM have generally shown poor efficacy, despite some signs of inducing some level of immune response against the GBM [16].…”
Section: Clinical Challenges In Treating Gbmmentioning
confidence: 99%
“…The BBB and relative immunologic privilege of the brain are doubtless factors in GBM ranking among the immunologically cold cancer types [ 15 ]. Clinical trials of various immunotherapeutic strategies in patients with GBM have generally shown poor efficacy, despite some signs of inducing some level of immune response against the GBM [ 16 ]. The immune system has some access and communication with the central nervous system (CNS) via glymphatic flow and lymphatics in the meninges [ 17 ], but in general it is somewhat compromised relative to that elsewhere.…”
Section: Clinical Challenges In Treating Gbmmentioning
confidence: 99%
“…Glioma is the most common primary intracranial tumor, and it is derived from neuroepithelium and accounts for 50%–60% of brain tumors ( Grady et al, 2022 ; O'Connor et al, 2021 ). At present, the clinical treatment of glioma mainly includes neurosurgical resection, radiotherapy, chemotherapy, and immunotherapy ( Grady et al, 2022 ). Nevertheless, patients have a mere median survival of 14 months, as well as a 5-year survival rate less than 10% ( Birk et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%